Criteria for evaluation of breastfeeding mobile applications: A scoping review - Leite , Renata de Araujo Meirelles; Pedron , Cecília Drebes; Bonatto , Vanessa Frighetto; Machado , Elisiane de Oliveira; Wachter , Djulia Andriele; Michielin , Fabiano da Costa; Bubols , Jessica Pinheiro; Vizini , Simone Thais; Santos, Suimara; Chassot , Maicon Daniel (Seven Editora, 2024)
Breastfeeding, in addition to involving a deep bond between mother and baby, is a process with several benefits for the child, such as: nutritional status, building immunity to prevent infections, physiology, and cognitive and emotional development. The use of applications, when properly guided by professionals in the area, contributes to the monitoring of clinical conditions, optimization of health, monitoring of possible risks, in addition to strengthening actions that promote health or identify factors that lead to the disease. Although the increase in the number of users of mobile technologies as a source of health promotion for pregnant women and babies is real, it is necessary to use evaluative methods to determine the real effectiveness in improving the lives of this population and how we could improve them. OBJECTIVE: To identify criteria for the evaluation of mobile applications on breastfeeding. METHOD: This is a scoping review. The identification of the studies was performed in the Virtual Health Library and National Library of Medicine databases. The Google Scholar tool and the reference lists of the studies were checked. The inclusion criteria were articles published in English and Portuguese from the last five years that responded to the proposed objective. Theses, dissertations, letters, and editorials were excluded. RESULTS: Of the 98 articles found in the databases, 15 studies were included in the review. The findings were divided into four relevant thematic axes: Scientific content; professional support; design and technology; and the user’s need for investment. They addressed guidance on barriers, contraindications, postpartum feelings, reliable content, professional advice, attractiveness, monitoring, practicality, and paid tools within the app. FINAL CONSIDERATIONS: Applications are current resources to assist in health education, however, they have gaps in terms of information quality, usability and affectivity. A checklist is needed for a better evaluation of these applications. DOI:https://doi.org/10.56238/sevened2024.001-001